Opsismodysplasia: Phosphate Wasting Osteodystrophy Responds to Bisphosphonate Therapy - Khwaja, Ansab; Parnell, Shawn E.; Ness, Kathryn; Bompadre, Viviana; White, Klane K. (Frontiers in Pediatrics, 2015)
We present two siblings affected with opsismodysplasia, a rare skeletal dysplasia caused by mutations in the INPPL1 gene. The skeletal findings include short stature with postnatal onset micromelia, marked platyspondyly, squared metacarpals, delayed skeletal ossification, metaphyseal cupping and postnatal micromelia. Respiratory compromise, delayed ambulation, and progressive lower extremity deformities are described. The severity of findings is variable. Renal phosphate wasting is associated with severe bone demineralization and a more severe phenotype. This report represents the first described cases of opsismodysplasia treated with intravenous bisphosphonate (pamidronate). Surgical management for lower extremity deformities associated with OPS is also reviewed.